Biosafety issues and opportunities for transgenic plants in Indian agriculture. (1st January 2002) - Ghosh, P.K.
The application of genetically modified plants in agriculture is anticipated to be a major event in evolving more productive and sustainable agriculture in the coming years. The concerns are the risks and the magnitude of the consequences to the environment. From the early 1990s, countries have imparted deregulated status to certain transgenic plants and products thereof, after "assessing" their risks. The assessment methods were, however, different in different countries, as no globally acceptable, generalised methods of assessment have yet evolved. The claimed advantage from the use of such transgenics in agriculture, along with pressure from commercial firms to be allowed to sell such transgenic seeds in other countries, is building up. These factors are urging the world community to evolve a universal biosafety protocol at the earliest opportunity. The general parameters needed to be considered for assessing biosafety and the measures required to manage the risks have been discussed. Besides scientific investigation, it has been suggested that all interested parties be brought together and involved in evaluating the biosafety protocols. A model proforma for collating information for evaluating the safety of transgenic plants by the regulatory agencies and the government has also been devised. Advances in research and applications in transgenic plants in Indian agriculture have also been discussed.